Practical WPF Charts and Graphics - Xu, Jack (Apress, 2012)
Welcome to Practical WPF Charts and Graphics. This book will provide all the tools you need to develop professional chart and graphics applications using the Windows Presentation Foundation (WPF) and C# based on the .NET Framework. I hope this book will be useful for WPF and C# programmers of all skill levels. We’ve all heard the saying “A picture’s worth a thousand words.” Charts and graphics play a very important role in every Windows application. They make data easier to understand, add interest to reports, and have wide applications in our daily life. The scientific, engineering, and mathematics community always has a need to present data and results graphically. Microsoft’s .NET platform with C# and WPF is one of the few and best development tools available for providing the computational capabilities both to generate data as a simulation engine and to display it in a variety of graphical representations based on the WPF graphics capabilityÿÿÿÿÿÿÿ